Pre-attentive fundamental frequency processing in Mandarin-speaking children with cochlear implants as revealed by the peak latency of positive mismatch response - Huang, Wanting; Wong, Lena L. N.; Chen, Fei (Frontiers in Neuroscience, 2022)
Fundamental frequency (F0) serves as the primary acoustic cue for Mandarin tone perception. Recent behavioral studies suggest that F0 information may be differently processed between Mandarin-speaking normal-hearing (NH) children and children with cochlear implants (CIs), which may partially explain the unsatisfactory outcome of lexical tone recognition using CIs with tonal language-oriented speech processing strategies. The aim of the current study was to provide neural evidence of F0 processing in Mandarin-speaking kindergarten-aged children with CIs compared with NH children. Positive mismatch responses (p-MMRs) to the change of the two acoustic dimensions of F0 (F0 contour and F0 level) in Mandarin-speaking kindergarten-aged children with CIs (n=19) and their age-matched NH peers (n=21). Effects of CI-related demographic factors (e.g., age at implantation, duration of CI use) on p-MMRs to F0 contour/F0 level change were also investigated. The two groups of children did not show any significant difference on the mean amplitude of p-MMR to either F0 contour or F0 level change. While the CI group exhibited a significantly shorter peak latency of p-MMR to F0 contour change than to F0 level change, an opposite pattern was observed in the NH group. No significant correlation was found between CI-related demographic factors and mean amplitude/peak latency of p-MMRs to F0 contour/F0 level change. This study revealed a higher sensitivity to F0 contour change than to F0 level change in children with CIs, which was different from that in NH children. The neural evidence of discrepant F0 processing between children with CIs and NH children in this study was consistent with the previously reported behavioral findings and may serve as a reference for the development and improvement of tonal language-oriented speech processing strategies.